The Impact of Principal Leadership on The Effectiveness of Learning in Christian Senior High School in Bandung, Indonesia - Junihot M. Simanjuntak (Universitas Kristen Satya Wacana, 2021)
The researcher wants to explain the impact of principal leadership on the effectiveness of learning at high school level. The study is aimed at finding principal leadership model as an ideal example in managing school as an educational institution to bring effective learning as an output. The results of the discussion show that the principal's leadership has a significant positive effect on teacher competence to realize the effectiveness of learning. The conclusion from this discussion that the effectiveness of learning can run well can be done by applying the leadership of the principal and teacher competence. The Principal has strong influence because he leads with love, gives positive impact on school even outside world. He has become catalyst agent who brings others to a purpose, by making himself as not only a creator of culture but also the one who sustains it especially inside school environment. The better the leadership of the principal is, the better the learning effectiveness at the school is.